Algebra-1 Problems

8.2 Substituting for a Variable


Problem #

Problem Statement

Problems Similar To

1.

Solve using substitution method.

\begin{equation}y=4x\textrm{ },\textrm{ }5x+6y=6\end{equation}

2.

Solve using substitution method.

\begin{equation}6x+y=5\textrm{ },\textrm{ }8x-6y=4\end{equation}

3.

Solve using substitution method.

\begin{equation}x=5-5y\textrm{ },\textrm{ }5x-4y=9\end{equation}

4.

Solve using substitution method.

\begin{equation}8x+6y=0\textrm{ },\textrm{ }2x+y=-5\end{equation}

5.

Solve using substitution method.

\begin{equation}-x+6y=-8\textrm{ },\textrm{ }7x+y=5\end{equation}

6.

Solve using substitution method.

\begin{equation}3x-y=-4\textrm{ },\textrm{ }8x-10y=-4\end{equation}

7.

Solve using substitution method.

\begin{equation}-x+9y=-8\textrm{ },\textrm{ }5x-10y=4\end{equation}

8.

Solve using substitution method.

\begin{equation}4x+4y=-28\textrm{ },\textrm{ }7x-y=-7\end{equation}

9.

Solve using substitution method.

\begin{equation}7x+7y=49\textrm{ },\textrm{ }(-2)x+2y=-6\end{equation}

10.

Solve using substitution method.

\begin{equation}5x+7y=7\textrm{ },\textrm{ }-35x+50y=-20\end{equation}

11.

Solve using substitution method.

\begin{equation}63x-7y=-21\textrm{ },\textrm{ }2x-10y=-10\end{equation}

12.

Solve using substitution method.

\begin{equation}y=x-10\textrm{ },\textrm{ }y=4x+3\end{equation}

13.

Solve using substitution method.

\begin{equation}y=4x+3\textrm{ },\textrm{ }y=10x-2\end{equation}

14.

Solve using substitution method.

\begin{equation}10x-y=2\textrm{ },\textrm{ }x+y=-4\end{equation}

15.

Solve using substitution method.

\begin{equation}10x+y=4\textrm{ },\textrm{ }y=x-7\end{equation}

16.

Solve using substitution method.

\begin{equation}10x+10y=0\textrm{ },\textrm{ }x+5y=-4\end{equation}

17.

Solve using substitution method.

\begin{equation}3x-5y=2\textrm{ },\textrm{ }x+7y=-5\end{equation}

18.

Solve using substitution method.

\begin{equation}(-6)x+y=0\textrm{ },\textrm{ }7x+5y=-3\end{equation}

19.

Solve using substitution method.

\begin{equation}\frac{1}{3} \times x+\frac{1}{4} \times y=6\textrm{ },\textrm{ }\frac{1}{6} \times x+y=6\end{equation}